NEGOSIASI NILAI RELIGIUS SISWA ANTARA LINGKUNGAN SEKOLAH DAN PAPARAN MEDIA DIGITAL - Fadillah, M Renaldy (IAI Sunan Giri Trenggalek, 2026)
The rapid development of digital technology has significantly influenced the formation of religious values among students at the elementary education level, including those in Islamic primary schools. Students are no longer limited to learning religious values from formal education and family environments, but are also exposed to diverse and sometimes conflicting values through digital media. This study aims to examine in depth how students negotiate religious values between the school environment and digital media exposure at MI Al Hasanah. This research employs a qualitative method with a case study approach. Data collection techniques include observation, in-depth interviews, and documentation. The participants consist of three students and one Islamic Religious Education (PAI) teacher selected purposively. Data validity is ensured through source triangulation and method triangulation techniques. The results of the study indicate that students possess a basic understanding of religious values through structured learning and habituation activities at school. However, the implementation of these values is not always consistent, especially outside the school environment. Students actively engage in a process of negotiating values when encountering digital content that differs from religious teachings, often balancing between personal interests and normative expectations. The study concludes that the formation of religious values is dynamic and influenced by both internal awareness and external digital exposure, highlighting the need for a more contextual and adaptive approach in Islamic education.